2015
DOI: 10.1017/s1368980015002839
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional status (as measured by height, weight and BMI) in Bangladesh: trends and socio-economic association over the period 1996 to 2007

Abstract: Objective: To analyse trends in maternal nutritional status in Bangladesh over a 12-year period and to examine the associations between nutritional status and socio-economic variables. Design: Maternal nutritional status indicators were height, weight and BMI. Socio-economic variables used were region, residency, education and occupation of the mothers and their husbands, house type, and possession score in the household. Setting: Bangladesh Demographic and Health Surveys (1996, 2000, 2004 and 2007) were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Our findings that socio-economic variables are important determinants of nutritional status are similar to those of earlier studies examining these associations in Bangladesh. Household wealth status (22,27,28) and higher educational attainment (7,(27)(28)(29)31,36,39,40) are wellestablished determinants of nutritional status. Like ours, earlier studies also reported that women in households with low socio-economic status experience a greater risk of underweight status and those in households with high socio-economic status experience a higher risk of being overweight/obese (27,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that socio-economic variables are important determinants of nutritional status are similar to those of earlier studies examining these associations in Bangladesh. Household wealth status (22,27,28) and higher educational attainment (7,(27)(28)(29)31,36,39,40) are wellestablished determinants of nutritional status. Like ours, earlier studies also reported that women in households with low socio-economic status experience a greater risk of underweight status and those in households with high socio-economic status experience a higher risk of being overweight/obese (27,41) .…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the relationship between selected socioeconomic and demographic variables and the nutritional status of under-five-year-old children in four Bangladesh Demographic Health Surveys conducted between 1996 and 2007. 199620002004199620002004199620002004 Stunted Wasted severely undernourised ( Z-score <-3.00)…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the most effective strategies for reducing the burden of malnutrition and accelerating development, it is important that the determinants of malnutrition are known (Mohsena et al, 2016). Moreover, the relationship between socioeconomic and demographic status and nutrition has important policy implications since international agencies currently tend to disregard nutritional status (as measured by anthropometry) as being a good predictor of poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study suggest that caution should be used when reporting only the mean as a summary measure, especially when improving health equity is a goal. Several studies have interpreted increases in mean as an indication of an improvement in health and development conditions [ 38 , 69 , 70 ]; however, this interpretation is only valid at a population level following the assumption that the variance stays constant around the mean. In our study, 26 countries exhibited an overall increase in mean height across birth cohorts, but our examination of the variance provides a much more nuanced picture.…”
Section: Discussionmentioning
confidence: 99%